Pengaruh Media Sosial, Teman Sebaya, dan Gaya Hidup terhadap Perilaku Konsumtif Siswa Jurusan Bisnis Ritel SMK Negeri 14 Jakarta - Nabila Anindhita; Nadya Fadillah Fidhyallah; Daru Putri Kusumaningtyas (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aimed to analyze the influence of social media, peer groups, and lifestyle on the consumptive behavior of Retail Business Department students at SMK Negeri 14 Jakarta, both partially and simultaneously. This study employed a quantitative method with a survey approach. The sample consisted of 140 respondents selected using the proportional random sampling technique. Data were collected through questionnaires and analyzed using IBM SPSS Statistics Version 24 with multiple linear regression analysis. The results showed that social media and lifestyle had a positive and significant influence on students’ consumptive behavior, while peer groups had no significant influence on consumptive behavior. Simultaneously, social media, peer groups, and lifestyle had a significant influence on students’ consumptive behavior. The Adjusted R Square value of 0.634 indicates that these three variables explain 63.4% of the variance in student consumptive behavior, while the remaining 36.6% is explained by other variables not examined in this study.